Social Eating Role in Ultra-Processed Food Consumption Among Urban Young Adults: The 2018 Indonesian Food Barometer - Arumsari, Imas; Putri, Nabilla Ayusyah; Lathifah, Siti Nur Lulu; Rosalba, Gita Aisyah Astrid; Khusun, Helda; Februhartanty, Judhiastuty; Aini, Rahmatika Nur (UI Scholars Hub, 2025)
This study investigated the differences in ultra-processed food (UPF), fruit, vegetable, and total fat consumption in different aspects of social eating among urban young adults. This cross-sectional study used the 2018 Indonesian Food Barometer dataset with 180 participants aged 18–25 years living in urban areas from 6 provinces in Indonesia. The data on social eating (cooking habits, eating out, and eating alone), UPF, fruits, and vegetables were obtained from an extended 24-hour food recall interview. The Mann-Whitney U test (CI 95%) was employed for data analysis. This study found that groups with less frequent cooking habits tended to have more total energy intake, fat intake, and total energy from UPF (p-value